DESIGN AND CONSTRUCTION OF 625KVAR POWER FACTOR CORRECTING PANEL - Olusolade, Micheal; Bello, Fasasi; Akinseye, Tope Akinbobola; Faweya, John Alesanmi (International Journal of Engineering Science Technologies, 2023)
In industry, most of the loads are inductive in nature which results in lagging power factor. This is the same for some commercial centers and homes with modern appliances, thus resulting in loss and wastage of energy leading to high power bills and heavy penalties from electricity boards in some developed countries. This electrical feature when low below certain values, below unity brings about low voltages, large copper loss, poor efficiency and hotness of the conductor used in the circuit. Power factor is the ratio of real or active power to apparent power. It is unit less. At unit (1) power factor, active and apparent power are equal. At this level, the reactive power is equal to zero and current is at minimum value. This 625kVar power factor correcting panel operates both manually and automatically for active load of 500kW at 0.8 power factors to bring it to 0.99 power factors. There are many ways to achieve this, but this project is employing only the use of capacitors and six capacitors were used. Conclusively, this design was successfully executed, and it is an indication that capacitors can be used to meet different initial and corrected power factor angle as losses were minimized hence reducing heat in the transformer, cables, and switch gear of the power system.